Chilean institutional policies and multi-level agents: Challenges from the COVID-19 pandemic and carbon footprint - Bergamini, Kay; Ojeda, Carolina G.; Gutiérrez, Patricia; Salazar, Gonzalo; Curillán, Christian (Frontiers in Communication, 2023)
Climate change of anthropogenic origin has become an inevitable presence. In this context, it has evolved into policies, frameworks for action and agreements that have been adopted from abroad without considering local realities. The implementation of policies aimed at climate change, particularly carbon footprint, was studied to observe this dissonance. The information collected in this study was coded, validated in internal workshops and compared with international references regarding carbon footprint policies. As a result, a disconnection was found among the different levels of action in terms of knowing the carbon footprint policies, identifying the responsibilities of the actors involved in carbon footprint decision-making and a lack of institutional adaptation to stressors such as pandemics.